BENTUK DAN SIFAT PENGABDIAN MASYARAKAT YANG DITERAPKAN OLEH PERGURUAN TINGGI - Herlina Emilia (Jurnal Pengabdian Kepada Masyarakat, 2022)
The drama of community service by universities is often connoted as an activity of providing free assistance and services to community groups who are weak, economically incapable, and are in a state of backwardness. Such connotations are the result of an error in interpreting the term "devotion". limited as a “selfless activity”. In fact, the activities of providing assistance and services are only one form of community service activities by universities, and do not always have to be done free of charge. In addition, all components of higher education organizations can carry out this community service dharma, because the implementation of this dharma is not only the duties and obligations of functional institutions such as the Community Service Institute which has been specially formed by universities. Lecturers (either individually or in groups), Laboratories, Departments, and Research Centers, can also carry out them according to the form of relevant service activities.